In memoriam: Yuriy Slynko (09.10.1961 – 14.07.2021) - Students, colleagues, and friends (A. O. Kovalevsky Institute of Biology of the Southern Seas of RAS, 2021)
On July 14, 2021, a talented, extraordinary, and purposeful ichthyologist Yuriy Vladislavovich Slynko passed away. Yu. Slynko left more than 250 scientific publications and 7 collective monographs.